Eco-Friendly Method Of Strawberry Cultivation At Rooftop Garden (International Journal of Food and Nutritional Sciences, 2022)
The present study deals with the exotic fruit Strawberry (Fragaria × ananassa) of the family Rosaceae, which has successfully acclimatized in the hot climatic conditions of south 24 parganas district of West Bengal, India. A decade ago, most of the strawberry farming was restricted in the hill areas of India (Awasthi, 2010)[1]. But in recent years strawberry cultivation is possible, in any Indian state adopting some specialized agricultural techniques. Strawberry is popular throughout the world not only for its characteristic aroma and attractive colour but also for its rich nutritional and medicinal values like vitamins, minerals, fibers and compounds with antioxidant and anti-inflammatory properties. It is a good source of phytochemicals like ellagic acid and a variety of flavonoids, such as anthocyanins, quercetin, kaempferol and catechin. The nutrients present in strawberries help to protect against heart diseases, stroke, cancer, high blood pressure, constipation and other diseases. However, the presence of pesticides in conventionally grown strawberries have many disadvantages like poor nutritional content, difference in taste, etc. Therefore, a novel method using age old techniques of homemade compost and organic fertilizers was applied for cultivation of strawberries and thus, selected optimum treatment for strawberry cultivation was standardized. The process was tested successively for the second, third, fourth and fifth year and then introduced to the local farmers for cultivation in the field. The increased nutritional value of strawberries will lead the farmers to earn good returns in near future. Also, the standardized method of cultivation will be more eco-friendly and economically viable than the contemporary methods.